Chemoprevention of Skin Carcinomas in High-Risk Transplant Recipients - Savoia, Paola; Zavattaro, Elisa; Cremona, Ottavio (Current Medicinal Chemistry, 2018)
Background: Long-term immunosuppressive therapy, as provided to solid organ transplant recipients, inevitably results in a significant inhibition of immune defenses; this leads to frequent skin infections and malignancies, which represent an important cause of morbidity and mortality for transplanted patients. The incidence and risk of skin carcinomas are elevated in solid organ transplant recipients in comparison with the general population, with a 10-fold increased risk for basal cell carcinoma and a 50-100-fold for squamous cell carcinoma. The schedule of immunosuppressive drugs influences the type and timing of skin malignancies, but a crucial role is also played by endogenous and exogenous risk factors. Methods & Results: Here, we will review the state-of-the-art in chemoprevention of epidermal carcinomas in order to provide useful information for clinicians involved in the management of transplant recipients. One-hundred and forteen paper, published on peerreviewed journals, has been included. Conclusion: Chemoprevention would be key in controlling skin carcinogenesis in high-risk patients.
Keywords: skin carcinomas